2021
DOI: 10.1039/d1ta02982g
|View full text |Cite
|
Sign up to set email alerts
|

Engineering membranes with macrocycles for precise molecular separations

Abstract: Macrocycles are a class of intrinsically porous organic molecules that can host guest molecules selectively. Owing to their diversified porous characteristics, host–guest/supramolecular feature, unique chemical versatility and tunable chemical functionalities,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 212 publications
(305 reference statements)
0
18
0
Order By: Relevance
“…Supramolecular compounds are considered to be advanced and efficient separation membrane building blocks due to the presence of intrinsic pores in their molecular structure. 27,28 The cucurbit[n]uril (CB[n]) family of molecular containers 29−31 displays powerful host−guest binding abilities toward hydrophobic cations in water, 32−36 which isolates the guests from the external environment. 37,38 Viologens and their derivatives are popular components of CB[n] (n = 7, 8)based complex functional systems like molecular machines, supramolecular polymers, and drug delivery systems.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supramolecular compounds are considered to be advanced and efficient separation membrane building blocks due to the presence of intrinsic pores in their molecular structure. 27,28 The cucurbit[n]uril (CB[n]) family of molecular containers 29−31 displays powerful host−guest binding abilities toward hydrophobic cations in water, 32−36 which isolates the guests from the external environment. 37,38 Viologens and their derivatives are popular components of CB[n] (n = 7, 8)based complex functional systems like molecular machines, supramolecular polymers, and drug delivery systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Supramolecular compounds are considered to be advanced and efficient separation membrane building blocks due to the presence of intrinsic pores in their molecular structure. , The cucurbit­[ n ]­uril (CB­[ n ]) family of molecular containers displays powerful host–guest binding abilities toward hydrophobic cations in water, which isolates the guests from the external environment. , Viologens and their derivatives are popular components of CB­[ n ] ( n = 7, 8)-based complex functional systems like molecular machines, supramolecular polymers, and drug delivery systems. Accordingly, we envisioned that formation of the CB[7]-BABD rotaxane complex would suppress dimerization of BABD cation radicals and improve the performance of the resultant NF membranes incorporating CBs. , Previously, we have presented the first examples of IP processes featuring CB­[ n ] rotaxanes as monomers. We found that the water permeability was enhanced threefold by reconfiguring the reconstructing membrane surface. , The design of voltage-gated membranes incorporating CB­[ n ] rotaxane monomers and investigations of their stimuli–response behavior remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…43 There has been increasing recent research on macrocycles-based nanochannel membranes, ranging from preparation methods to applications. 44 However, more recognition and understanding of membrane separations should be gained with the rising requirement of practical application. In this section, host-guest nanochannel membranes with the applications of separation are primarily discussed.…”
Section: Host-guest Nanochannels With Separation Featuresmentioning
confidence: 99%
“…Reverse osmosis and nanofiltration membranes, for example, are essential to desalinize water, and high-performance semipermeable membranes are necessary for the development of high current densities batteries and fuel cells. These were only two examples of many that one could think about, but there are many other applications for this kind of membrane such as artificial skin, dialysis systems, gas purification and separation, clean rooms air filters, and many more [1][2][3][4][5]. Solid-state synthetic membranes (SSSM) occupy a big share of these markets, since they may be produced in many sizes with specific characteristics and properties.…”
Section: Introductionmentioning
confidence: 99%
“…When dispersed in polymer masses, cavitands form aleatoryoriented hollow segments, through which small chemical species can hop and move across the polymer mass. This kind of membrane may be used for many specific applications among those we have mentioned above, like sensors, batteries, and ionselective electrodes [2,[6][7][8][9]. Our group has produced several cavitand-loaded solid-state polymeric membranes this way, using resorcin[n]arenes, cucurbit[n]urils, bambus[n]urils, and hemicucurbit[n]urils to explore this property, and to test different cavitands regarding their selectivity and other characteristics [10,11].…”
Section: Introductionmentioning
confidence: 99%